EMPLOYEE PERFORMANCE IN TERMS OF GENDER IN ACCOUNTING UNDERSTANDING - Wibowo, Agung Edy; L. Tobing, Vargo Christian (Universitas Putera Batam, 2024)
Company needs to properly record its accounting activities. Accounting helps in the preparation of accurate financial reports, which serve as the basis for strategic decision-making. Accounting also functions as a tool for control and evaluation. Through accounting, organizations can monitor financial performance regularly and make necessary adjustments to achieve business objectives. Therefore, understanding accounting helps organizations maintain their financial health and prevent bankruptcy. Accounting knowledge is important in fulfilling legal and tax obligations. Failure to meet these obligations can result in significant legal sanctions and fines, ultimately harming the company. This study aims to analyze the performance differences of employees involved in the accounting process within a company. From the study's sample analysis, it was proven that there are no significant performance differences in accounting understanding between male and female workers